Correlations of Self-Efficacy among Women with Gestational Diabetes - F Bastani; R Zarrabi (Tehran University of Medical Sciences, 2011)
Background & Aim: Gestational diabetes is a major concern during pregnancy. Psychological factors such as self-efficacy play important role in adherence of the treatment, control of blood glucose, and the outcomes of the pregnancy. The main purpose of this study was to determine correlations of self-efficacy in women with gestational diabetes attending to educational medical centers of Iran University of Medical Sciences in Tehran. Methods & Materials: In this descriptive correlational study, we recruited 100 women aged 15-49 years old with gestational diabetes and singleton pregnancies using consecutive sampling method. Data were collected using Diabetic Self-Efficacy scale. Results: The mean age of the women was 31 years. The majority of the women (66%) had moderate economic status and more than half (60%) had no higher education. Sixty eight percent of the study participants were obese or overweight. About 33% of the participants were nullipara and 69% had wanted pregnancies. The results showed that 43% of the women had low self-efficacy. The self-efficacy scores were significantly correlated with education (P=0.005) and occupation (P=0.016). Conclusion: Self-efficacy is an important determinant of self-management and self-control in gestational diabetes. Regarding low self-efficacy among the women, it seems that implementing educational-counseling strategies to enhance self-efficacy can be helpful to promote optimum self-care among women with gestational diabetes